Vascular response to experimental stent malapposition and under-expansion - O’BRIEN, CAROLINE C. (Ann Biomed Eng, 2016)
BACKGROUND: Up to 80% of all endovascular stents have malapposed struts, and while some impose catastrophic events others are inconsequential. METHODS AND RESULTS: Thirteen stents were implanted in coronary arteries of seven healthy Yorkshire pigs, using specially-designed cuffed balloons inducing controlled stent malapposition and under-expansion. Optical coherence tomography (OCT) imaging confirmed that 25% of struts were malapposed (strut-wall distance< strut thickness) to variable extent (max. strut-wall distance malapposed group 0.51±0.05mm versus apposed group 0.09±0.05mm, p=2e-3). Imaging at follow-up revealed malapposition acutely resolved (<1% of struts remained malapposed at day 5), with strong correlation between lumen and the stent cross-sectional areas (slope =0.86, p<0.0001, R(2)=0.94). OCT in three of the most significantly malapposed vessels at baseline showed high correlation of elastic lamina area and lumen area (R(2)=0.96) suggesting all lumen loss was related to contraction of elastic lamina with negligible plaque/intimal hyperplasia growth. Simulation showed this vascular recoil could be partially explained by the non-uniform strain environment created from sub-optimal expansion of device and balloon, and the inability of stent support in the malapposed region to resist recoil. CONCLUSIONS: Malapposition as a result of stent under-expansion is resolved acutely in healthy normal arteries, suggesting existing animal models are limited in replicating clinically observed persistent stent malapposition.